METHODOLOGICAL-DIDACTIC PRINCIPLES OF FORMING THE CREATIVE ACTIVITY OF PRESCHOOL CHILDREN - Sadikova Zinnura; Urinova Feruza Uljayevna (Galaxy International Interdisciplinary Research Journal, 2022)
Activities to develop the creative abilities of preschool children play an important role in the formation of the child’s personality. All the studies conducted by scientists and psychologists in this field prove that children with creative abilities have a more stable spirit, communicate with them and have a friendly relationship.